2012
DOI: 10.1100/2012/578251
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin: Local Application in Implant-Associated Infection and Complicated Osteomyelitis

Abstract: Background. The rise of highly resistant bacteria creates a persistent urge to develop new antimicrobial agents. This paper investigates the application of the lipopeptide antibiotic daptomycin in infections involving the human bone.Methods. Compressive and tensile strength testing of daptomycin-laden PMMA was performed referring to the ISO 5833. The microstructure of the antibiotic-laden PMMA was evaluated by scanning electron microscopy. Intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Rosslenbroich et al. used a continuous flow chamber to check elution kinetics, and the bacteria tested were S. epidermidis and E. faecium only . Elution of antibiotics from acrylic cement was thought to be a surface phenomenon and little of the antibiotic contained within the matrix was released .…”
Section: Discussionmentioning
confidence: 99%
“…Rosslenbroich et al. used a continuous flow chamber to check elution kinetics, and the bacteria tested were S. epidermidis and E. faecium only . Elution of antibiotics from acrylic cement was thought to be a surface phenomenon and little of the antibiotic contained within the matrix was released .…”
Section: Discussionmentioning
confidence: 99%
“…71 Recently, daptomycin has also been recommended as a new option for the treatment of implant infections, 68 due to its good effect systemically and locally against methicillin-resistant staphylococci and enterococci in patients with implant-associated infections. 72,73 By using such antibiotic treatment, prosthetic knee-associated infections in many patients could be well controlled. 42 Soriano et al ., 74 in a study of 85 patients with orthopedic implant infections, reported that 47- and 60-day treatment with linezolid showed a 72.2% and a 42.8% success rate in acute and chronic infections, respectively, when the implant was not removed.…”
Section: Treatment Of Prosthesis-related Infectionsmentioning
confidence: 99%
“…One potential therapeutic strategy is local drug delivery where antibiotics delivered locally at the implant site in high concentration can take care of pathogenic bacteria. This can be achieved either by using an adequate carrier or by coating the implants (stainless steel or titanium implants) with polymers loaded with antimicrobial agent [ 11 – 13 ]. Large number of delivery strategies have been used till date.…”
Section: Introductionmentioning
confidence: 99%